Skin Cancer – educational interventions – primary care and secondary care - Ward, Amelia (2010)
Abstract Background Skin cancer is the most common cancer in humans, and its incidence is escalating rapidly. The need for accurate skin cancer diagnosis is essential to minimise the associated morbidity and mortality, and subsequently improve patient outcomes.